Sport Tourism: Understanding the Concept, Recognizing the Value (The Gaze: Journal of Tourism and Hospitality, 2013)
The study of sport tourism has become very popular in the western countries. Therefore, it is aimed at grasping the knowledge of sport tourism from those studies: its nature, scope, significance, concepts, theories, approaches, models, perspectives and paradigms. This paper is intended to provide a broad understanding of sport tourism and its implications to the people who are involved in the tourism industry. It is believed that activities in sport and tourism build social capital by bringing people together and establishing their relationship. In this way they are making the world a smaller place contributing to greater understanding between different cultures, tolerance and ultimately, to world peace with a focus on adventure sport tourism. The study of sport tourism is equally important in the context of Nepal because it is one of the popular destinations for adventure sport tourists and tourism. This paper discusses on water sport in terms of whitewater river rafting tourism in the context of Nepal, which is still ignored and untouched in the field of academia.The Gaze: Journal of Tourism and Hospitality Vol.5 2013 pp.13-42